A survey of O RhD‐negative red cells in the South West: stocks and distribution compared to use and wastage. Issue 2 (13th February 2014) - Page, J.; Jones, A.; MacRate, E.; Webb, M.; Birchall, J.; ,
SUMMARY Background O RhD‐negative (ONeg) red cells can be used in an emergency for recipients of other blood groups. Matching supply and demand is currently a challenge; therefore, any service redesign, using more remote blood fridges, must consider ONeg red cell availability. Objectives To identify whether the number of fridges stocking emergency ONeg units correlates with use and wastage. Methods The number and distribution of ONeg red cells was requested from the hospitals in South West England. For NHS Hospitals, comparison was made with ONeg National Health Service (NHS) organisation – NHS Blood and Transplant (NHSBT) issues (ONeg as a proportion of all red cells), wastage and the proportion of ONeg units given to ONeg patients (ONeg‐to‐ONeg use). Correlations were performed using Spearman's rank correlation coefficient. Results Of the 23 hospitals, 21 responded. Four hundred and forty three ONeg units were held across the region – 56% as stock and the remaining as emergency units. ONeg issues increased with the number of fridges holding emergency units (ρ = 0·48, significance 0·046). No correlation was found between the number of fridges and ONeg wastage or ONeg‐to‐ONeg use. A longer unit shelf life on rotation back to stock was associated with lower wastage (ρ = −0·597, significance 0·009). Conclusions Although there was a weak correlation between fridge numbers and overall percentage ONeg use, there was no correlation with ONeg wastage.